Differential risk of incident Alzheimer’s disease dementia in stable versus unstable patterns of subjective cognitive decline - Wolfsgruber, Steffen; Weyerer, Siegfried (Journal of Alzheimer's disease, 2016)
Background: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer’s disease (AD) dementia. Objective: We tested the mo